Intercultural Dialogue in the Meeting on Neutrosophy and Latin American Worldviews: A Perspective from the Náhuat Indigenous Chair of the Technological University of El Salvador - Morena Guadalupe Magaña (Neutrosophic Sets and Systems)
This article presents a reflective analysis of the intercultural forum held during the Meeting on Neutrosophy and Latin American Worldviews, focusing on the contribution of the Náhuat Indigenous Chair at the Technological University of El Salvador. Drawing on philosophical and decolonial frameworks, it explores how the revitalization of the Náhuat language serves as both an act of cultural resistance and an epistemological statement. The Chair's initiatives—including teacher training, language certification, and community-based educational projects—are examined as concrete expressions of intercultural commitment. These efforts are contextualized within a broader critique of historical erasure, media manipulation, and social forgetting that have affected Indigenous identities in El Salvador. The paper proposes that the dialogue between neutrosophy and Indigenous cosmovisions enables the construction of inclusive, pluralistic knowledge systems capable of challenging hegemonic narratives. The integration of neutrosophic logic with ancestral worldviews opens pathways for rethinking education, identity, and cultural memory from a Global South perspective.